2017
DOI: 10.1159/000453618
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Rituximab Combined with <sup>131</sup>I for Ophthalmic Outcomes of Graves' Ophthalmopathy Patients

Abstract: Purpose: The purpose of this study is to examine the effectiveness of introducing both rituximab (RTX) and 131I for active Graves' ophthalmopathy (GO) with hyperthyroidism. Methods: In total, 217 patients suffering from active GO with hyperthyroidism were included in this research. All subjects were randomly assigned to 3 groups. Patients in group A solely received 131I treatment; group B1 underwent a methylprednisolone treatment in combination with 131I treatment; and group B2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 25 publications
(38 reference statements)
0
36
0
Order By: Relevance
“…Of those, 19 were not RCTs, 21 were reviews, eight evaluated different comparisons, four were animal studies, and one was a clinical practice guideline. Thus, four trials were eligible for inclusion in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of those, 19 were not RCTs, 21 were reviews, eight evaluated different comparisons, four were animal studies, and one was a clinical practice guideline. Thus, four trials were eligible for inclusion in this meta‐analysis …”
Section: Resultsmentioning
confidence: 99%
“…The methodologic quality of the included trials is summarized in Table . All four studies reported acceptable methods of randomization . Two studies did not describe the blinding of patients and outcome assessors .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations